Professional Identity of Physical Education Teachers : What Does It Consist Of? - Junhyuk Park; Euichang Choi (Korea Institute of Sport Science, 2023)
PURPOSE Professional Identity Formation (PIF) has become a core concept in various professional education fields as it emphasizes professionals' dispositions as well as abilities. This study provides an overview of PIF and explores the characteristics of professional education programs that highlight PIF. Through this overview, the purpose of this study is to propose the 'Professional Identity Matrix for Physical Education Teacher (PIMPET)', which helps identify PE teachers' Professional Identity (PI). METHODS This study suggests a guideline to understand PE teachers' PI based on the analysis of the current literature on PI and PIF. RESULTS The characteristics of PIF-based professional education programs were described according to three criteria: teaching content, method, and assessment. On the PIMPET framework, the components of PI formed by PE teachers can be categorized into nine domains which encompass the three identity dimensions (competence, knowledge, and disposition) and the three task areas (teaching, student, and administration). CONCLUSIONS The PIMPET framework allows for a comprehensive understanding of PE teachers' PI and provides implications for the professionalism of PE teachers and PE teacher education.